2013
DOI: 10.1002/stem.1466
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of β-catenin activity is required to stabilize self-renewal of rat embryonic stem cells

Abstract: Stabilization of b-catenin, through inhibition of glycogen synthase kinase 3 (GSK3) activity, in conjunction with inhibition of mitogen-activated protein kinase kinase 1/2 (MEK) promotes self-renewal of na€ ıve-type mouse embryonic stem cells (ESC). In developmentally more advanced, primed-type, epiblast stem cells, however, b-catenin activity induces differentiation. We investigated the response of rat ESCs to b-catenin signaling and found that when maintained on feeder-support cells in the presence of a MEK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 43 publications
4
33
0
Order By: Relevance
“…We note that the amount of GSK3i used influenced culture stability such that cells selfrenewed in 0-2 μM GSK3i, whereas 5 μM drove differentiation. This varies from mESCs, where 3 μM GSK3i is optimal (3), but is similar to observations made with naïve rat ESCs, for which 1 μM GSK3i is optimal (22,23). Excess GSK3i may enable Wnt-induced nuclear events that are counter to the naïve state.…”
Section: Discussionsupporting
confidence: 65%
“…We note that the amount of GSK3i used influenced culture stability such that cells selfrenewed in 0-2 μM GSK3i, whereas 5 μM drove differentiation. This varies from mESCs, where 3 μM GSK3i is optimal (3), but is similar to observations made with naïve rat ESCs, for which 1 μM GSK3i is optimal (22,23). Excess GSK3i may enable Wnt-induced nuclear events that are counter to the naïve state.…”
Section: Discussionsupporting
confidence: 65%
“…We supposed that this phenomenon was due to use of the GSK3 inhibitor, CHIR99021, during rPSC cultivation. This is in agreement with previous studies [33][34][35] that demonstrated that GSK3 inhibition led to activation of some differentiationassociated genes, including several trophoblast-specific genes. Similar to rPSCs, mouse ESCs and iPSCs were recently discovered to give rise to trophoblast cells due to Cdx2 overexpression [43], indicating the existence of common transcriptional mechanisms that regulate lineagespecific differentiation in rats and mice.…”
Section: Discussionsupporting
confidence: 93%
“…It was described that use of a GSK3 inhibitor, CHIR99021, in cultivation of rat and mouse ESCs caused ectopic expression of Cdx2 [33][34][35] encoding a wellknown trophoectodermal transcription factor [36]. According to RT-PCR and transcriptome analysis, Cdx2 was not expressed in the rEF lines and was highly expressed (on the average, 1,192 normalized read counts) in the rat pluripotent cells (Fig.…”
Section: Transcriptome Analysismentioning
confidence: 98%
“…Importantly, we demonstrated that GRP78 downregulation was accompanied with the decreased expression of c-Myc and β-catenin (both are well characterized oncogene and stemness markers). Importantly, c-Myc has been characterized as one of the key factors for the maintenance of stem cell pluripotency and generation of cancer stem cells [31]; β-catenin, in addition, also has been indicated in different cancer types as a powerful oncogene and factor for stabilizing self-renewal ability [32,33]. The concomitant decreased expression of both c-Myc and β-catenin as the result of GRP78 down-regulation in GBM cells suggests a novel interaction between these molecules.…”
Section: Discussionmentioning
confidence: 99%